Synthesis and characterisation of cycloruthenated benzhydrazone complexes: catalytic application to selective oxidative cleavage of olefins to aldehydes. Issue 99 (11th October 2016) - Manikandan, Thimma Sambamoorthy; Ramesh, Rengan; Semeril, David
Abstract : The synthesis and structural characterisation of cyclometalated ruthenium(ii ) aroylhydrazone complexes have been described. The complexes were developed as effective catalysts for oxidative cleavage of olefin reactions. Abstract : A simple and convenient method to synthesise new air-stable cyclometalated ruthenium(ii ) complexes from the reaction of p -substituted acetophenone benzhydrazide ligands and [RuHCl(CO)(AsPh3 )3 ] has been described. The complexes have been characterised by various methods, including elemental analysis, FT-IR, NMR ( 1 H and 13 C) and UV-vis. The molecular structures of complexes3 and4 have been determined by singlecrystal X-ray diffraction analysis which indicates the tridentate coordination mode of the ligand and the presence of a distorted octahedral geometry around the ruthenium ion. The complexes have been found to be a highly active catalytic system in the selective oxidative cleavage of a wide range of alkenes and alkynes in the presence of NaIO4 as an oxidant. Notably, the desired aldehyde products were obtained with high conversions and yields using 0.5 mol% catalyst loading within 30 min at room temperature. Furthermore, the influence of reaction parameters such as solvents, oxidants, temperature and catalyst loading was also investigated.